1986
DOI: 10.1080/03079458608436273
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐linked feathering alleles(k, k+)in chickens of diverse genetic backgrounds

Abstract: SUMMARYChicks were produced for this experiment by mating males from a broiler parent stock that were heterozygous (K/k+) at the sex-linked feathering locus with early feathering (fc+/w) females. Dams were from three diverse lines -White Plymouth Rocks selected for high or low 8-week, body weight and White Leghorns selected for high antibody response to sheep erythrocytes. Escherichia coli (E. coli) were injected into the caudal air sac of some chickens and others were maintained as uninoculated controls. Body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
3

Year Published

1996
1996
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
3
0
3
Order By: Relevance
“…The strain of chickens used in the present study were bred specifically so that the flight feathers of female chicks grow faster than those of males, as a cue for determining the sex of hatchlings. A series of sex-linked alleles are reported to influence various other traits such as growth rate, sexual maturity, and the rate of survival (Dunnington et al 1986;Tamura et al 1987). It is therefore critically important to examine whether similar sex differences also occur in other birds of the order Galliformes such as quails, which have been less selectively bred than domesticated chickens.…”
Section: Ecological Accounts Of Sex Differencesmentioning
confidence: 99%
“…The strain of chickens used in the present study were bred specifically so that the flight feathers of female chicks grow faster than those of males, as a cue for determining the sex of hatchlings. A series of sex-linked alleles are reported to influence various other traits such as growth rate, sexual maturity, and the rate of survival (Dunnington et al 1986;Tamura et al 1987). It is therefore critically important to examine whether similar sex differences also occur in other birds of the order Galliformes such as quails, which have been less selectively bred than domesticated chickens.…”
Section: Ecological Accounts Of Sex Differencesmentioning
confidence: 99%
“…It has been reported that in addition to being associated with LF development, the K allele is associated with other effects, such as reduction of egg production and increasing the mortality rate (Somes 1975, Harris et al 1984, Dunnington et al 1986, Smith & Fadly 1988, O'Sullivan et al 1991. Some adverse effects are probably associated with the presence of the endogenous retrovirus 21 (ev21) gene; our preliminary study (G Bu, G Huang, H Fu, J Li, S Huang & Y Wang, unpublished observations) demonstrated that ev21 is likely to be located in the first intron of the dPRLR (or PRLR) gene, at the K locus in LF chickens (Bacon et al 1988, Smith & Fadly 1988, Boulliou et al 1992, while some negative side effects can be attributed to the presence and expression of dPRLR gene according to the findings of previous studies and the present study (Elferink et al 2008, Wang et al 2010a.…”
Section: Potential Association Of the Dprlr Gene With The Lf Developmmentioning
confidence: 99%
“…White Leghorn layers produced more antibodies than two White Rock broiler populations when vaccinated at 20-36 days-of-age, but one of the broiler lines generated the highest titres after early or late vaccination (12 or 44 days-of-age) (Peleg, Heller & Pitkovsky, 1985). Another experiment with three types of crossbreds observed that age at exposure to APEC affected whether lesion scores differed between progeny types (Dunnington, Siegel & Gross, 1986). An interaction between host genetics and feeding protocol (ad libitum versus alternate-days) was demonstrated after APEC challenge of two broiler breeder lines and White Rock x White Leghorn crosses (Boa-Amponsem, O'Sullivan, Gross, Dunnington & Siegel, 1991;Praharaj, Gross, Dunnington & Siegel, 1996).…”
Section: Phenotypic Differencesmentioning
confidence: 99%